Robust steering control in rack steering vehicles using cascaded finite-time prescribed performance with output mapping and anti-windup PI control - Norsharimie, Mat Adam; Mohd Iskandar Putra, Azahar; Mohd Herwan, Sulaiman; Addie Irawan, Hashim (2026)
The paper presents a robust control strategy for enhancing steering precision and yaw stability in rack steering vehicle (RSV) by integrating a Finite-Time Prescribed Performance Control with Output Mapping and an Anti-windup Proportional-Integral (FPPCM-API) controller. The proposed two-loop cascaded architecture addresses the limitations of conventional PID and FT-PPC controllers by simultaneously regulating steering angle (yaw dynamics) within a bounded-error framework. The outer loop ensures finite-time convergence of yaw tracking error through a smooth, bounded transformation, while the inner loop employs an anti-windup PI controller to mitigate actuator saturation. Simulation results under the disturbances (9-10 Hz) and payload demonstrate that FPPCM-API significantly outperforms a benchmark FTPPC-API controller in trajectory tracking and robustness. Notably, it achieves a 66.7% reduction in rise time, an 87.4% improvement in transient response, and lower lateral displacement errors across varying yaw inertias. Although an increase in initial overshoot is observed, it does not compromise path accuracy or system stability. The proposed control scheme thus offers a high-performance solution for precision path-following advanced automotive steering applications.